The rights of the Orang Asli under the federal constitution of Malaysia - Hamzah, Hamimah; Kadouf, Hunud Abia (IIUM Press, 2011)
Malaysia is a federation ofthinccn Slales.'ll has a total land mass of 329.847 square kilometCTS separated by the South China Sea into two region", namely. Peninsular Malaysia and Malaysian Borneo.' Mala)'Sia has a di\'l'rs~y ofI'llIC.'CS in a population ofabout 28,5 million in 2010 ofwhich 22,5 million are in the Peninsular. 2.5 million in Sarawak and 3.2 million in Sabah.'ln the Peninsuhr, the IX'pulation is made up ofthree main ethnic groups, viz; Malays. Chinese aod Indians. On the other hand, tbe OrangAsli form only 0.6 per CCllt of the country's population, which renders thcmasan ethnic minority. According to the2006eensus. the entire populationofOrangAsli was a mere 141.230